The legitimate use of military force the just war tradition and the customary law of armed conflict - Hensel, Howard M. (Justice, international law and global security, 2008)
Throughout human history, scholars, statesmen and military leaders have attempted to define what constitutes the legitimate use of armed force by one community against another. This volume brings together an internationally recognized team of scholars to explore the philosophical and societal foundations of just war tradition